Familial silence surrounding HIV and non-disclosure of HIV status to older children and adolescents. Issue 7 (3rd July 2018) - McHugh, Grace; Simms, Victoria; Dziva Chikwari, Chido; Mujuru, Hilda; Nathoo, Kusum; Chonzi, Prosper; Munyati, Shungu; Dauya, Ethel; Bandason, Tsitsi; Busza, Joanna; Ferrand, Rashida A
ABSTRACT: Increasing numbers of children with HIV are surviving to adolescence and beyond, many of whom are orphaned. Disclosure of childrens' and adolescents' HIV status has been shown to improve adherence and retention in HIV treatment programmes. We investigated caregiving arrangements and intra-familial experience of HIV and its relationship to HIV disclosure to older children and adolescents. Children aged 6–15 years, newly diagnosed with HIV infection or previously diagnosed but not engaged in HIV care, were recruited from seven primary care clinics in Harare, Zimbabwe. Their caregivers responded to a nurse-led questionnaire. Family history of HIV, disclosure of HIV status to the child and reasons for non-disclosure were ascertained. The association between sociodemographics, caregiving, family HIV history and other characteristics and non-disclosure of HIV status to the child was determined using univariate and multivariate logistic regression. We recruited 385 participants, median age = 11 years (IQR: 9–13); 52% were female. Disclosure had occurred in 79% of children aged 11–15 years and 19% of children aged 6–10 years. Age under 11 years (adjusted OR [aOR] = 18.89, 95% confidence interval [CI] = 10.64–33.55; p < 0.001), being male [aOR]= 2.56, 95% CI = 1.49–4.54; p = 0.001, being unaware of the parents' HIV status [aOR]= 32.42, 95% CI = 13.19–79.71; p < 0.001, and being newly diagnosed [aOR]= 2.52, 95% CI = 1.29–4.91; p = 0.007, were independently associated with non-disclosure. Disclosure outside of the family occurred infrequently and included friends of family (7%), school teacher (8%), school headmaster (4%) and church pastor (6%). High non-disclosure rates were present as well as a lack of discussion about HIV within the family. Disclosure outside of family was low reflecting difficulty in caregivers' ability to discuss HIV with their child or surrounding community. HIV programmes need to support families in the disclosure process.